Pengaruh Efektivitas Sistem Informasi Akuntansi Pada Kinerja Karyawan Dengan Budaya Organisasi dan Dukungan Manajemen Puncak Sebagai Pemoderasi - Salsabilla Amalia Prapta Deadewi; Gede Juliarsa (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Technological developments will have an impact on government agencies. Therefore, the ability to compete is needed in order to minimize and neutralize the occurrence of an obstacle. This study aims to determine the effect of the effectiveness of accounting information systems on employee performance with organizational culture and top management support as a moderator. The population in this study amounted to 188 people. The method used is nonprobability sampling with a purposive sampling technique so that a total sample of 51 respondents is obtained. The data analysis technique uses the Moderated Regression Analysis (MRA) Test. The results of testing the first hypothesis indicate that the variable effectiveness of accounting information systems has a positive effect on employee performance. The results of testing the second hypothesis indicate that organizational culture as a moderator weakens the effect of the effectiveness of accounting information systems on employee performance. The results of testing the third hypothesis indicate that top management support as a moderator weakens the effect of the effectiveness of accounting information systems on employee performance.